Analysis of disaster events in Serang City seen from the number of victims and damage - Nofebrianti, Nutrisia; Asmayawati, Asmayawati; Wafi, Muhamad; Wahyudi, Wahyudi (Institute of Computer Science (IOCS), 2024)
Disasters are natural events that we do not know precisely when they will occur. In Serang City, some disasters that usually occur are related to the seasons in Indonesia, namely the rainy and dry seasons. These disasters include floods, droughts, collapsed houses, landslides, lightning strikes, and fires. This study aims to determine the types of disasters that occur in the city of Serang. In addition, to find out the casualties and damage affected by the disaster. This research was conducted using a qualitative method with descriptive research type based on data issued by BPBD Serang City. The type and source of data used is secondary data. The results of this study showed that there have been 1,083 disaster events in the last three years in Serang. The disasters were floods, collapsed houses, lightning-struck houses, fires, landslides, and droughts. The total number of injured victims was 18, and the number of affected victims was 40,140, while the total damage caused by the disaster was 591 damages